당뇨병 환자의 구강질환과 구강건강관리 실태 - 최혜숙; Hye Sook Choi; 정영란; Young Ran Jung (Han'guk Ch'iwisaeng Hakhoe chi, 2015)
Objectives: The aim of this study is to investigate the relationship between diabetes mellitus and oral disease in the Korea adults by using the representative data of Korea National Health and Nutrition Examination Survey (KNHANES) V. Methods: Using data from a cross-sectional survey of Korea National Health and Nutrition Examination Survey V. The subjects were 5,602 adults over 19 years old. The survey data and the examination data are used for the independent variables. KNHANES included health status, nutrition survey, and oral examination. The health status was obtained by a self-reported questionnaire of the study subjects and direct interview was carried out on economic status, prevalence rate, and use of medical services. Results: The regular dental checkup of diabetes patients was significantly lower than the general population. Regular dental visits allow adults to receive early diagnosis and obtain restorative care at the first visit. The regular annual oral examination is very important to prevent and manage the chronic diseases including diabetes mellitus. Conclusions: Diabetes mellitus can be fully prevented and managed by the regular annual dental checkup. The establishment of the regular dental checkup system can prevent and manage the complication due to diabetes mellitus and other chronic diseases.